Cutaneous vasculitis: Lessons from COVID-19 and COVID-19 vaccination - Corrà, Alberto; Verdelli, Alice; Mariotti, Elena Biancamaria; Ruffo di Calabria, Valentina; Quintarelli, Lavinia; Aimo, Cristina; Sunderkötter, Cord H.; Caproni, Marzia (Frontiers in Medicine, 2022)
Cutaneous vasculitis (CV) is an inflammatory skin-limited vascular disease affecting the dermal and/or hypodermal vessel wall. From the pathogenetic point of view, idiopathic forms are described as well as the induction from various triggers, such as drugs, infections, and vaccines. Following SARS-CoV-2 pandemic outbreak, cases of CV induced by both COVID-19 and COVID-19 vaccinations have been reported in literature. The aim of our work was to collect multiple cases available in the literature and analyze the frequency of the different forms of induced vasculitis, as well as their histological and immunopathological features. Although rare, CV induced by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and vaccines may provide interesting insights into the pathogenesis of these inflammatory processes that may in the future be useful to understand the mechanisms underlying cutaneous and systemic vasculitis.